PENGARUH PENERAPAN MODEL PEMBELAJARAN PROBLEM BASED LEARNING TERHADAP KEMAMPUAN PEMECAHAN MASALAH MATEMATIS PESERTA DIDIK KELAS VIII - Arzi, Ghina Haifa (Jurnal Edukasi dan Penelitian Matematika, 2023)
This study was conducted to acquire the ability of mathematical problem solving of student in mathematics, the part of learning mathematics, conducted at SMPN 1 Batusangkar. The result of the first test of math problem-solving skills was that the student did not solve the problem well. One solution to overcome this is the application of problem-based learning models. The research results shown that mathematical problem-solving skills who learn to use problem-based learning outperform those who learn to use direct learning. Initial tests of mathematics problem-solving ability shown that the students did not solve the problem well. One attempt to overcome this is the use model of problem-based learning. The research result shown that those who learn to use problem-based learning have better problem-solving skills in mathematics than those who learn to use direct learning. Keywords. – Problem Based Learning, The Ability of Mathematical Problem Solving